HERMENEUTICAL STUDY OF ΠΑΡΟΥΣΊΑ AND ITS SIGNIFICANCE TO THE 21ST CENTURY CHRISTIANS - M. O. Oyetade (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2020)
The Old Testament furnishes its readers with two pictures of Christ’s coming: his coming to earth as a servant in glorious apparel and his coming to earth as a king in glorious apparel. This has brought about bewilderment both to the Jews who expected only the kingly and glorious Christ and the 21st century Christian who are being misled by some preachers and teachers of the Gospel of Christ. The objective of this paper, therefore, is to unearth two forms of Christ’s second coming: (1) a secret coming – as a thief in the night, and (2) public, universal coming, when every eye shall see him. Therefore through lexicosemantics analysis which reveals, its root-words and word-stems and the various possible semantic categories created by the human mind, this paper claims that the secret coming of Christ is what is called the rapture and the public coming is called the παρουσία. It conveys the idea that Christ’s return will be a definite and decisive action on his part. He will come himself, as surely as he came in the incarnation.